2016
DOI: 10.4236/ait.2016.64005
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of the Sense Egypt Platform for Real-Time Analysis of IoT Data Streams

Abstract: Nowadays, we experience an abundance of Internet of Things middleware solutions that make the sensors and the actuators are able to connect to the Internet. These solutions, referred to as platforms to gain a widespread adoption, have to meet the expectations of different players in the IoT ecosystem, including devices [1]. Low cost devices are easily able to connect wirelessly to the Internet, from handhelds to coffee machines, also known as Internet of Things (IoT). This research describes the methodology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The key requirements for IoT analytics architectures are the ability to handle big data problems in terms of different 'v's such as velocity, variety and volume [3,4,5,6,7] in real-time [3,4,6,7,8,13]. While the precise definition of real-time computing is rather subjective and varies depending on the use case [16], we found that in terms of IoT analytics it is closely linked to the value of the information to be derived from data processing.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…The key requirements for IoT analytics architectures are the ability to handle big data problems in terms of different 'v's such as velocity, variety and volume [3,4,5,6,7] in real-time [3,4,6,7,8,13]. While the precise definition of real-time computing is rather subjective and varies depending on the use case [16], we found that in terms of IoT analytics it is closely linked to the value of the information to be derived from data processing.…”
Section: Motivationmentioning
confidence: 99%
“…Looking at smart home environments, different use cases such as home security as well as disaster detection and prevention require at least low latency [17]. In this regard, time criticalness of analytics scenarios and the need for low latency of data processing in IoT environments was also frequently named in previous research [3,4,6,7]. Furthermore, the integration of the data from a multitude of sources must be possible [3,7,18].…”
Section: Motivationmentioning
confidence: 99%
See 3 more Smart Citations